Kontribusi Istri Sebagai Pencari Nafkah - Fajriyati, Nadiya; Najib, Rofiqun; Zulkarnain, Rifaldi (el Buhuth: Borneo Journal of Islamic Studies, 2023)
In the sakinah family consensus, it is the wife's responsibility to take care of children and needs in the kitchen. However, with the development of the times, the roles in the family often change, and this tendency has even become a hereditary custom among the people of Wonorejo Village, Poncokusumo District, Malang Regency. Wonorejo city has a lot of potential in an industrial area, many industrial cigarette factories, spear and apple plantations are often used as a livelihood for women. Only they don't know that earning a living is the husband's duty and responsibility. This problem has become a trend in Wonorejo village, they don't understand the law of the problem, so they often do it. Therefore, it is necessary to understand women's contribution to family livelihoods from the perspective of the Syafi'i school of thought.This research adopts the empirical research type and adopts the qualitative research method. The results of this study show that the majority of women in the village of Wonorejo contribute directly to the generation of household income. Imam Syafi'i explained several livelihood indicators commonly used by men, 2 mud for the rich, 1 mud for the poor and 1.5 for the middle class. So much so that you can see in the context of women's contributions that a woman's ability to work must be based on a man's enjoyment, with a clear purpose.